Design of Horizontal Well Program for Ajeel Field - S.AL-Jawad, Mohammed; AL-Dabaj, A.A.; Abdul Hadi Abdul Hussien, Hassan (Iraqi Journal of Chemical and Petroleum Engineering, 2014)
Horizontal wells are of great interest to the petroleum industry today because they provide an attractive means for improving both production rate and recovery efficiency. The great improvements in drilling technology make it possible to drill horizontal wells with complex trajectories and extended for significant depths. The aim of this paper is to present the design aspects of horizontal well. Well design aspects include selection of bit and casing sizes, detection of setting depths and drilling fluid density, casing, hydraulics, well profile, and construction of drillstring simulator. An Iraqi oil field (Ajeel field) is selected for designing horizontal well to increase the productivity. Short radius horizontal well is suggested for the developing the field since many drilled vertical wells are exists A soft string model was programmed to predict the imposed loads on suggested drillstring. Six operating conditions of drillstring includes rotating off bottom, pick up without rotation, slack off without rotation, pick up with rotation, slack off with rotation, and sliding ,were considered. Also, two buckling modes of drill string were estimated. According to drillstring simulator results, short radius well of build rate 90 deg/100 ft could be implemented without exceeding the strength limits of the suggested drillstring.